2018
DOI: 10.1016/j.compstruct.2018.06.074
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of non-uniform gelation effects on residual stresses of thick laminates based on tailed FBG sensor

Abstract: Due to the appearance of temperature gradient and non-uniform gelation, fully understanding of residual stresses is even more complex in thick laminates. In this paper, basic mechanisms of cure process were presented firstly. Then, experimental investigation of the non-uniform gelation was carried out together with characterization of necessary material properties. Tailed FBG sets were applied to monitor the cure of thick laminates with temperature gradient. The non-uniform gelation and chemical shrinkage grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The use of embedded fiber optic sensors in laminates is still very prevalent with many examples of this technique being successfully applied to the monitoring of internal strains during cure in thermosets [ 102–105 ] and thermoplastics [ 57, 106, 107 ] where a higher operating temperature is required. Another key benefit of fiber optic sensors is that they can often be repurposed after cure as condition monitoring devices.…”
Section: Nondestructive Methodsmentioning
confidence: 99%
“…The use of embedded fiber optic sensors in laminates is still very prevalent with many examples of this technique being successfully applied to the monitoring of internal strains during cure in thermosets [ 102–105 ] and thermoplastics [ 57, 106, 107 ] where a higher operating temperature is required. Another key benefit of fiber optic sensors is that they can often be repurposed after cure as condition monitoring devices.…”
Section: Nondestructive Methodsmentioning
confidence: 99%
“…Cure induced residual stresses arise within the part due to thermal expansion anisotropy, resin shrinkage and tool-part interaction. [1][2][3][4] The influence of the cureinduced residual stresses on the manufactured part is twofold. On one hand, experimental studies have shown the influence of residual stresses upon mechanical performances of the final part could be beneficial with respect to longitudinal and transverse tensile strength [5][6][7] and delamination properties 8,9 and detrimental in the case of in-plane shear strength.…”
Section: Introductionmentioning
confidence: 99%
“…Although carbon fiber reinforced plastic (CFRP) are widely used in new generation airframe structures such as for the Airbus A350XWB and Boeing 787, it is still difficult to manufacture precisely large-scale CFRP structures and ensure their structural integrity during operation. Due to thermalchemical-mechanical interactions, thermal expansion mismatch, chemical cure shrinkage and toolparts interactions during the manufacturing process, composite components tend to deviate more from their designed geometrical configuration than metallic ones [1][2][3][4]. Counteracting these undesired manufacturing distortions and geometric deviations for composite structures is still a challenge for manufacturers.…”
Section: Introductionmentioning
confidence: 99%